Research assessment landslide and sedimentation of Hoa Binh hydropower reservoir - Thom, Bui Van; Son, Pham Quang; Hung, Pham Van; Anh, Ngo Thi Van (Vietnam Journal of Earth Sciences, 2016)
This work presents the research results lakeshore landslides and sedimentation Hoa Binh hydropower reservoir by synthetic methods analyze high-resolution satellite images, survey, surveying and mapping. Lakeside landslide occurred under different levels in space. Landslides lakeshore strong level includes the following sections: section from Ban Khoc to Cua Sap and Yen Phong to the dam. Landslides lakeshore average level includes the following sections: from town It Ong to the Ta Bu, from Chieng Hoa until Ban Khoc and from Ba Sen to Yen Phong. Weak levels include segments: from Ta Bu to Chieng Hoa and Suoi Lua to Ba Sen. Evolution of Hoa Binh reservoir sedimentation are classified into 3 sections with diferent levels. Level is critical for the passage from Ban Trang to Ban Khoc, accounting for 5.78% amount of alluvium. Strong level of about passage from Ban Khoc to Suoi Lua, accounting for 77.9% volume of alluvium. The average level of the period from Suoi Lua to the dam, the volume of alluvium 16.3%. After more than 20 years of Peace reservoirs in operation and exploitation (1989-2013), sediment deposition has lost 37% of dead storage, in the middle lake was filling both the useful capacity. Hoa Binh hydropower reservoir fairly strong, with different levels in space. Clips lakes fluctuate strongly from Cua Sap to Suoi Lua; Strong: from Yen Phong to the dam; Average: from Ban Khoc to Cua Sap and from Ba Sel to Yen Phong; weak: from Son La dam to It Ong, from Hin Pha to Ban Khoc and from Suoi Lua to Ba Sel; Very weak: from It Ong to Hin Pha. References Nguyễn Tứ Dần và nnk, 2007: Sử dụng tư liệu viễn thám đa thời gian và GIS, nghiên cứu sự biến động lớp phủ trên lưu vực sông Đà góp phần giám sát bồi tích hồ Hòa Bình. Báo cáo tổng kết đề tài cấp Viện Khoa học và Công nghệ Việt Nam. Giai đoạn 2006 - 2007. Viện Hàn lâm Khoa học và Công nghệ Vệt Nam. Richard, Jon A, 1986: Remote Sensing Digital Image Analysis - And Introduction. Springer, Verlag. Sabins F.F, 1978: Remote Sensing - Principles and Interpretation. San Francisco. Nguyễn Kiên Dũng, 2002: Nghiên cứu xây dựng cơ sở khoa học tính toán bồi lắng cát bùn hồ chứa Hòa Bình, Sơn La. Luận án tiến sĩ, Hà Nội. Trần Trọng Huệ và nnk, 2000: Nghiên cứu đánh giá hiện tượng trượt lở khu vực mép nước hồ Hoà Bình, kiến nghị một số giải pháp phòng tránh. Báo cáo đề tài cấp Viện Hàn lâm KH&CN Việt Nam. Nguyễn Trọng Yêm và nnk, 2006: Nghiên cứu thành lập bản đồ tai biến thiên nhiên trên lãnh thổ Việt Nam. Báo cáo tổng kết đề tài, Viện Địa chất, Hà Nội. Đào Văn Thịnh và nnk, 2005: Các tai biến địa chất ở Tây Bắc Bộ. Báo cáo tổng kết đề tài, Cục Địa chất và Khoáng sản Việt Nam, Hà Nội.